Control Preference and Financial Attributes: Founders as CEOs in Small, Publicly Traded Firms - William R. Lane; Mel Jameson (Journal of Small Business Finance, 1993)
Existing theories of the firm are silent with respect to cross-sectional differences in performance or characteristics of firms attributable to different types of managers. We hypothesize that the investment, financing and dividend decisions of founders differ systematically from those of nonfounder managers as a result of 1) founders valuing control more highly than do nonfounders, a condition we refer to as the control retention effect, and 2) founders being associated with younger, faster growing firms, a condition we label the life cycle effect. Our findings are that both effects are at work, but in different decision areas. No evidence is found that founders exploit their status to extract higher direct compensation.
Keywords: L25; G34; G32; 650; Control Preference; Founder; CEO; Small Firm; Publicly Traded